Oscillation criteria for second order nonlinear neutral differential equations - Hasanbulli, Mustafa; Rogovchenko, Yuri V. (Elsevier Science Inc, 2010)
By refining the standard integral averaging technique, we obtain new oscillation criteria for a class of second order nonlinear neutral differential equations of the form (r(t)(x(t) + p(t)x(t - tau))')' + q(t)f(x(t), x(sigma(t))) - 0. Assumptions in our theorems are less restrictive, whereas the proofs are significantly simpler compared to those in the recent paper by Shi and Wang [18] and related contributions to the subject. Examples are provided to illustrate the relevance of new theorems. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Nonlinear neutral differential equations; Second order; Asymptotic behavior; Oscillatory solutions; Integral averaging